PENGARUH TRANSPARANSI, AKUNTABILITAS DAN FAIRNESS LAPORAN KEUANGAN PEMERINTAH DAERAH (LKPD) TERHADAP PENCEGAHAN KORUPSI PEMERINTAH DAERAH (Studi Empiris pada Pemerintah Daerah di Pulau Jawa) - Lailatul Khikmah; Agus Purwanto (Diponegoro Journal of Accounting, 2023)
This study aims to test and analyze empirically the effect of transparency, accountability, and fairness of local government financial reports (LKPD) on the prevention of local government corruption. This research was conducted because it saw the provision of an unqualified opinion (WTP) by the Supreme Audit Agency (BPK) which showed a better presentation of local government financial statements (LKPD) but cases of corruption in local governments continued to increase.This research was conducted by quantitative analysis method with data collection method conducted with secondary data. The source of transparency data is obtained from the website of each Regency/City Government in Java Island in the last three years. Accountability data is obtained from the follow-up data on Audit Results Recommendations (TLRHP) published by BPK RI. Fairness data is obtained from opinions issued by the BPK RI Representatives of each region through inspection reports (LHP). Prevention of local government corruption is obtained based on corruption cases from 2018 to 2020 which have permanent legal force and are not allegations of corruption obtained from the Indonesian KPK. The sample in this study is the same as the population that has been determined by criteria (purposive sampling), so this research can be said to be a census. A total of 357 samples were analyzed using multiple regression analysis with the help of SPSS.The results of this study indicate that the variables of transparency, accountability, and fairness have a negative effect on preventing corruption in local government. So, transparency, accountability and fairness have not been able to become a factor in preventing local government corruption.